2008
DOI: 10.3171/jns/2008/109/8/0268
|View full text |Cite|
|
Sign up to set email alerts
|

Bevacizumab and irinotecan therapy in glioblastoma multiforme: a series of 13 cases

Abstract: The combination of bevacizumab and irinotecan is safe and has excellent activity even in this relapsed, heavily pretreated population of patients with high-grade malignant glioma, most of whom would not be candidates for clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 13 publications
3
35
0
Order By: Relevance
“…27,28,32,[38][39][40][41][42][43][44][45][46][47] In addition, several retrospective studies have also been reported combining bevacizumab and irinotecan; carboplatin; carboplatin and cetuximab; carboplatin, etoposide, and ifosfamide; lomustine; carmustine; etoposide; or temozolomide. [48][49][50][51][52][53][54][55][56][57][58] Although these small studies are not easily compared due to their size and various patient populations, the consensus to date has been that no combination significantly surpasses the outcomes of bevacizumab monotherapy for recurrent glioma. 9 …”
Section: Early Study Of Bevacizumab In Patients With Recurrent Glioblmentioning
confidence: 99%
“…27,28,32,[38][39][40][41][42][43][44][45][46][47] In addition, several retrospective studies have also been reported combining bevacizumab and irinotecan; carboplatin; carboplatin and cetuximab; carboplatin, etoposide, and ifosfamide; lomustine; carmustine; etoposide; or temozolomide. [48][49][50][51][52][53][54][55][56][57][58] Although these small studies are not easily compared due to their size and various patient populations, the consensus to date has been that no combination significantly surpasses the outcomes of bevacizumab monotherapy for recurrent glioma. 9 …”
Section: Early Study Of Bevacizumab In Patients With Recurrent Glioblmentioning
confidence: 99%
“…[5][6][7][8][9][10][11]29,30 Although gliomas are certainly at the extreme end of a spectrum with respect to infiltrative growth, it was recently shown that targeting of the angiogenic pathway also in subcutaneous xenografts leads to enhanced invasive growth and metastases. 31,32 Such adverse effects are not expected to occur when directing therapy against the existing tumor vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4 The occurrence of angiogenesis in GBM has been rationale for extensive testing of angiogenesis inhibitors. However, a number of phase II studies have now revealed that, despite inducing a radiological response, these inhibitors do not prolong overall survival and allow disease progression, 5,6 likely because diffuse infiltrative growth is angiogenesis independent and provides a mechanism of escape from anti-angiogenic therapies. [4][5][6][7][8][9][10][11] The phenotypic differences that exist in GBM are reflected in the vasculature, which is highly heterogeneous.…”
mentioning
confidence: 99%
“…Chemotherapy is used in combination with radiation and may help prolong patient survival. Combining an angiogenesis inhibitor (such as bevacizumab) with a chemotherapeutic agent (irinotecan) may achieve better results (16,74). In theory, a cytotoxic and an anti-angiogenic agent may complement each other and be more effective in decreasing tumor cell proliferation, inducing cancer cell death and reducing tumor-associated inflammation (72).…”
Section: Current Perspectivesmentioning
confidence: 99%
“…This disease is more common among men compared to women and less common among black compared to Caucasian populations (4,16). Only ~5% of the patients have a family history of the disease (17) and the only known risk factor is exposure to ionizing radiation (18).…”
Section: Introductionmentioning
confidence: 99%